Surprising Comparative Properties of Monetary Models: Results from a New Model Database - Taylor, John B.; Wieland, Volker (The Review of Economics and Statistics, 2012)
In this paper, we investigate the comparative properties of empirically estimated monetary models of the U.S. economy using a new database of models designed for such investigations. We focus on three representative models due to Christiano, Eichenbaum, and Evans (2005), Smets and Wouters (2007), and Taylor (1993a). Although these models differ in terms of structure, estimation method, sample period, and data vintage, we find surprisingly similar economic impacts of unanticipated changes in the federal funds rate. However, optimized monetary policy rules differ across models and lack robustness. Model averaging offers an effective strategy for improving the robustness of policy rules.